Analisis kegiatan penggemukan kepiting bakau (Scylla serrata) di Desa Tanjangawan pada Musim Barat dan Musim Timur - Armansyah, Dimas; Safitri, Nur Maulida; farikhah, farikhah (Fishery Product Technology Study Program, Yudharta University, Pasuruan, 2024)
Introduction: This study aims to determine the differences in fattening results for mud crabs during the west and east seasons.. Method: The research was conducted in Tanjangawan Village, Ujungpangkah District, Gresik Regency, using an exploratory descriptive research method. A total of three ponds with a total of four plots were studied in the west and east seasons, namely in June 2021, December 2021, and May-July 2022. Data collection was carried out in the form of primary data collection using observation, interviews, and active participation. Data were analyzed using Microsoft Excel 2013.The fattening ratio of mud crabs in the west season and the east season was analyzed by t-test (Î±=5%). Result: The results of this study obtained from data analysis of the Specific Growth Rate of Mud Crabs (Scylla serrata) in Tanjangawan Village, Ujungpangkah District, Gesik Regency, it was found that the growth rate from the west season was higher (1.2%) compared to the growth rate from the east season (0.41%). The survival value in the west season is 95% higher than the east season, with a value of 92.8%. Conclusion: The different conditions between in the west season and east season obtained in this study indicate mud crabs have larger carapace width and weight in the west season due to increased sunlight exposure.